Expected Architects Acceptance of a BIM Tool to Optimize the Building Energetic Performance. - Noriega, Paulo (2020)
Universidade de Lisboa, Faculdade de Arquitetura, CIAUD, Rua Sá Nogueira, Pólo Universitário, Alto da Ajuda, 1349-055, Lisboa, Portugal - In Advances in Ergonomics in Design - Proceedings of the AHFE 2020 Virtual Conference on Ergonomics in Design